Role of Caspase-8 and Fas in Cell Death After Spinal Cord Injury - Sobrido-Cameán, Daniel; Barreiro-Iglesias, Antón (Frontiers in Molecular Neuroscience, 2018)
Spinal cord injury (SCI) causes the death of neurons and glial cells due to the initial mechanical forces (i.e. primary injury) and through a cascade of secondary molecular events (e.g. inflammation or excitotoxicity) that exacerbate cell death. The loss of neurons and glial cells that are not replaced after the injury is one of the main causes of disability after SCI. Evidence accumulated in last decades has shown that the activation of apoptotic mechanisms is one of the factors causing the death of intrinsic spinal cord cells following SCI. Although this is not as clear for brain descending neurons, some studies have also shown that apoptosis can be activated in the brain following SCI. There are two main apoptotic pathways, the extrinsic and the intrinsic pathways. Activation of caspase-8 is an important step in the initiation of the extrinsic pathway. Studies in rodents have shown that caspase-8 is activated in spinal cord glial cells and neurons and that the Fas receptor plays a key role in its activation following a traumatic SCI. Recent work in the lamprey model of SCI has also shown the retrograde activation of caspase-8 in brain descending neurons following SCI. Here, we review our current knowledge on the role of caspase-8 and the Fas pathway in cell death following SCI. We also provide a perspective for future work on this process, like the importance of studying the possible contribution of Fas/caspase-8 signalling in the degeneration of brain neurons after SCI in mammals.